Pan-Genome and Comparative Genome Analyses of Propionibacterium acnes Reveal Its Genomic Diversity in the Healthy and Diseased Human Skin Microbiome - Shuta Tomida (American Society for Microbiology, 2013)
ABSTRACT Propionibacterium acnes constitutes a major part of the skin microbiome and contributes to human health. However, it has also been implicated as a pathogenic factor in several diseases, including acne, one of the most common skin diseases. Its pathogenic role, however, remains elusive. To better understand the genetic landscape and diversity of the organism and its role in human health and disease, we performed a comparative genome analysis of 82 P. acnes strains, 69 of which were sequenced by our group. This collection covers all known P. acnes lineages, including types IA, IB, II, and III. Our analysis demonstrated that although the P. acnes pan-genome is open, it is relatively small and expands slowly. The core regions, shared by all the sequenced genomes, accounted for 88% of the average genome. Comparative genome analysis showed that within each lineage, the strains isolated from the same individuals were more closely related than the ones isolated from different individuals, suggesting that clonal expansions occurred within each individual microbiome. We also identified the genetic elements specific to each lineage. Differences in harboring these elements may explain the phenotypic and functional differences of P. acnes in functioning as a commensal in healthy skin and as a pathogen in diseases. Our findings of the differences among P. acnes strains at the genome level underscore the importance of identifying the human microbiome variations at the strain level in understanding its association with diseases and provide insight into novel and personalized therapeutic approaches for P. acnes-related diseases. IMPORTANCE Propionibacterium acnes is a major human skin bacterium. It plays an important role in maintaining skin health. However, it has also been hypothesized to be a pathogenic factor in several diseases, including acne, a common skin disease affecting 85% of teenagers. To understand whether different strains have different virulent properties and thus play different roles in health and diseases, we compared the genomes of 82 P. acnes strains, most of which were isolated from acne or healthy skin. We identified lineage-specific genetic elements that may explain the phenotypic and functional differences of P. acnes as a commensal in health and as a pathogen in diseases. By analyzing a large number of sequenced strains, we provided an improved understanding of the genetic landscape and diversity of the organism at the strain level and at the molecular level that can be further applied in the development of new and personalized therapies.